2005
DOI: 10.1002/glia.20196
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Aquaporin 4 in rodent spinal cord: Relationship with astrocyte markers and chondroitin sulfate proteoglycans

Abstract: Water balance between cells and extracellular compartments is essential for proper functioning of the central nervous system, as demonstrated by its perturbations in pathological conditions. Aquaporin 4 (AQP4) is the predominant water channel in brain and spinal cord, where it is present mainly on astrocytic endfeet contacting vessels. A role in water homeostasis control has been proposed also for the extracellular matrix, that in brain consists mainly of chondroitin sulfate proteoglycans (CSPGs). Using cytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 64 publications
7
40
0
1
Order By: Relevance
“…All reports have shown that AQP4 water channels are primarily expressed in spinal cord astrocytes, surrounding blood vessels and neurons (Vitellaro-Zuccarello et al, 2005;Rash et al, 1998Rash et al, ,1999Oshio et al, 2004). Consistent with those reports, we found robust expression of AQP4 in astrocytes forming barriers between the spinal cord parenchyma and blood or cerebrospinal fluid: in astrocytic processes surrounding blood vessels or in glia limitans externa and interna.…”
Section: Astrocytic Localization Of Aqp4 In the Uninjured And Injuredsupporting
confidence: 91%
“…All reports have shown that AQP4 water channels are primarily expressed in spinal cord astrocytes, surrounding blood vessels and neurons (Vitellaro-Zuccarello et al, 2005;Rash et al, 1998Rash et al, ,1999Oshio et al, 2004). Consistent with those reports, we found robust expression of AQP4 in astrocytes forming barriers between the spinal cord parenchyma and blood or cerebrospinal fluid: in astrocytic processes surrounding blood vessels or in glia limitans externa and interna.…”
Section: Astrocytic Localization Of Aqp4 In the Uninjured And Injuredsupporting
confidence: 91%
“…The MER was accompanied by expression of AQP4 that was in parallel with GFAP changes. In spinal cord white matter, the overlap between AQP4 and GFAP is almost complete (Vitellaro-Zuccarello et al, 2005), suggesting that AQP4 is a binding partner of GFAP. Actin is a dynamic astrocytic cytoskeletal element (Wang and Hatton, 2007b).…”
Section: Suckling-evoked Gfap Reexpansion By Transiently Increasing Ementioning
confidence: 99%
“…For double-labeling experiments, mAbs to ECM components were used in combination with one of the following polyclonal rabbit antibodies: anti-calretinin (1:1,500), anticalbindin D-28k (1:1,500), and anti-parvalbumin (1:3,000), all from Swant (Bellinzona, Switzerland), used to label various subpopulations of local association neurons (Ren and Ruda 1994;Carr et al 1998); anti-potassium channel Kv3.1b subunit (Sigma; 1:250), considered a marker of fast-firing neurons (Rudy and McBain 2001;Baranauskas et al 2003); anti-aquaporin-4 (AQP4, Sigma; 1:800) identifying the main water channel expressed in the CNS (Amiry-Moghaddam and Ottersen 2003) and used to visualize astrocyte plasma membranes (Vitellaro-Zuccarello et al 2005). Motor neurons were labeled with mAb SMI 32 against a non-phosphorylated epitope of the neurofilament H subunit (NF-H, Sternberger Monoclonals, Lutherville, Md., USA; 1:500).…”
Section: Antibodies and Other Markersmentioning
confidence: 99%